Profitabilitas Memoderasi Good Corporate Governance Dan Nilai Perusahaan Perbankan Di Bursa Efek Indonesia - Dewi, Putu Pande R. Aprilyani; Indraswari, I Gusti Agung Ayu Pramita (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Good company value can be said to be an illustration that the company is able to guarantee prosperity and provide welfare for its shareholders. By implementing good corporate governance, it is hoped that the company will be more transparent and careful in managing the company so that it can be more efficient in carrying out its duties to increase company profits and maximize company value. The research was conducted at banking companies listed on the Indonesia Stock Exchange in 2019-2021. Where the population of this study was 46 companies and the sample was determined using purposive sampling so that a sample size of 60 banking companies was obtained. The results of this research show that good corporate governance has no effect on company value, while profitability strengthens the influence of good corporate governance on company value.  Keyword: good corporate governance, company value, profitability